Block copolymers containing polyacrylamide and polyacrylic acid: Bulk structure and hydrogen bonds system. (2nd January 2017) - Kunitskaya, L.; Zheltonozhskaya, T.; Destarac, M.; Mazieres, S.
ABSTRACT: Asymmetric block copolymers PAAc- b -PAAm (DBCs) and PAAm- b -PAAc- b -PAAm (TBCs) comprised poly(acrylic acid) blocks of constant chain length and polyacrylamide blocks of variable chain length were synthesized using RAFT/MADIX technique. Their properties in a bulk state were studied by differential scanning calorimetry and the hydrogen bond system was investigated by Fourier transform infrared spectroscopy. It was found that DBCs and TBCs possess a homogeneous amorphous structure, whose temperatures of glass transition and destruction beginning increased with growth of PAAm block length. The H-bond system between PAAc and PAAm blocks was most developed in TBC sample and formed manly by the mixed cyclic dimmers of carboxyl and amide groups.